Study of the characteristics of combined of blockboards made of post-consumer wood - Lesiv, L.E. (Forestry, Forest, Paper and Woodworking Industry, 2022)
Reasonably, wood resources should be used comprehensively, in particular, this applies to wood waste and residues at all stages of production. But today, more than ever, the question of processing post-consumer wood (PCW) has arisen – an additional reserve of wood that has already lost its consumer characteristics in products. It is proposed to use it in the production of structural panel materials, in particular for the production of traditional and normative carpentry boards in factory conditions. Designs of carpentry ordinary and combined blockboards from PCW, obtained from dismantled windows, doors and house structures, are proposed. A batch of carpentry boards from PCW was made by implementing the B-plan of the second order, where the variables were the width of the rails of the inner shield, and the rails were made of wooden bars and sawn strips of particleboard (PB). From the obtained experimental plates measuring 440x440 mm, samples were obtained for testing strength indicators during static bending. A regression model of the dependence of the initial strength parameters during static bending depending on the width of the rails of the combined carpentry blockboards from PCW resources. The models are adequate. It was established that the mechanical characteristics of all carpentry blockboards from PCW resources, regardless of their design, meet the requirements of DIN 68705-2:2014-10. Based on the results of experimental studies, it was established that the highest mechanical parameters are characterized by the combined carpentry blockboards made of PCW of the following designs in terms of rail width: BPCW = 30 mm; BPB = 30 mm – strength index during static bending – 32.252 MPa. It has been established that the highest mechanical indicators are characterized by 4 mm plywood-faced carpentry blockboards with a glued shield made of PCW and a combined carpentry blockboards with a glued shield made of PCW and PB. When the width of the rails is 50 mm, the average strength during static bending of such plates is 27.88 and 25.211 MPa, respectively. It is calculated that the use of BPCW gives financial and environmental benefits, namely, that carpentry blockboards made of BPCW (312 UAH) are 17-23% cheaper than similar ones made of primary wood (378 UAH).